Solid electrolyte material and battery using the same

By optimizing the composition of Li, Ca, Y, Sm, X and O in solid electrolyte materials, especially by adjusting the O molar ratio in the surface area and the overall area, the problem of insufficient lithium ion conductivity in the prior art is solved. It achieves efficient battery charging and discharging and safety improvements.

CN115280425BActive Publication Date: 2025-02-14PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202180021336.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-03-31
Filing Date
2021-01-25
Publication Date
2025-02-14
Estimated Expiration
2041-01-25

AI Technical Summary

Technical Problem

The prior art is difficult to provide solid electrolyte materials with high lithium ion conductivity, which affects the charge and discharge characteristics and safety of the battery.

Method used

A solid electrolyte material including Li, Ca, Y, Sm, X and O is used, wherein X is at least one selected from F, Cl, Br and I, and the total molar ratio of O in the surface region to Y and Sm The total molar ratio of O to Y and Sm in the whole is greater.

Benefits of technology

It achieves high lithium ion conductivity, improves the charging and discharging characteristics and safety of the battery, and avoids the production of hydrogen sulfide.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115280425B_ABST
    Figure CN115280425B_ABST
Patent Text Reader

Abstract

The present disclosure relates to a solid electrolyte material comprising Li, Ca, Y, Sm, X and O, wherein X is at least one selected from F, Cl, Br and I, and the molar ratio of O to the total of Y and Sm in the surface region of the solid electrolyte material is greater than the molar ratio of O to the total of Y and Sm in the entire solid electrolyte material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a solid electrolyte material and a battery using the same. Background Art

[0002] Patent Document 1 discloses a solid-state battery using a sulfide solid electrolyte. Patent Document 2 discloses a solid-state battery using Li 6-3z Y z A solid electrolyte material represented by X6 (satisfying 0<z<2, and X is Cl or Br).

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2011-129312

[0006] Patent Document 2: International Publication No. 2018 / 025582 Summary of the invention

[0007] Problems to be solved by the invention

[0008] An object of the present disclosure is to provide a solid electrolyte material having high lithium ion conductivity.

[0009] Means for solving problems

[0010] The solid electrolyte material disclosed in the present invention is a solid electrolyte material containing Li, Ca, Y, Sm, X and O, wherein X is at least one selected from F, Cl, Br and I, and the molar ratio of O to the total of Y and Sm in the surface region of the solid electrolyte material is greater than the molar ratio of O to the total of Y and Sm in the entire solid electrolyte material.

[0011] Effects of the Invention

[0012] The present disclosure provides a solid electrolyte material having high lithium ion conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 A cross-sectional view showing a battery 1000 according to a second embodiment.

[0014] Figure 2 It is a graph showing the X-ray diffraction patterns of the solid electrolyte materials of Examples 1 to 4.

[0015] Figure 3 A schematic diagram showing a press mold 300 used to evaluate the ion conductivity of a solid electrolyte material.

[0016] Figure 4Graph showing a Cole-Cole plot of the solid electrolyte material of Example 1 obtained by impedance measurement.

[0017] Figure 5 It is a graph showing the initial discharge characteristics of the batteries of Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0018] Below, while referring to the attached Figure 1 Embodiments of the present disclosure will be described.

[0019] (First embodiment)

[0020] The solid electrolyte material of the first embodiment includes Li, Ca, Y, Sm, X, and O. Here, X is at least one selected from F, Cl, Br, and I, and the molar ratio of O to the total of Y and Sm in the surface region of the solid electrolyte material is greater than the molar ratio of O to the total of Y and Sm in the entire solid electrolyte material.

[0021] The solid electrolyte material of the first embodiment has high lithium ion conductivity. Here, high lithium ion conductivity refers to, for example, 1×10 -5 S / cm or more. That is, the solid electrolyte material of the first embodiment may have, for example, 1×10 -5 S / cm or higher ion conductivity.

[0022] The surface region of the solid electrolyte material in the first embodiment refers to a region extending from the surface of the solid electrolyte material to a depth of about 5 nm in the inner direction.

[0023] The solid electrolyte material of the first embodiment can be used to obtain an all-solid battery having excellent charge and discharge characteristics. The all-solid battery may be a primary battery or a secondary battery.

[0024] The solid electrolyte material of the first embodiment preferably does not contain sulfur. A solid electrolyte material that does not contain sulfur does not generate hydrogen sulfide even when exposed to the atmosphere, and therefore has excellent safety. The sulfide solid electrolyte disclosed in Patent Document 1 can generate hydrogen sulfide when exposed to the atmosphere.

[0025] The solid electrolyte material of the first embodiment may also be substantially composed of Li, Ca, Y, Sm, X and O. "The solid electrolyte material of the first embodiment is substantially composed of Li, Ca, Y, Sm, X and O" means that in the solid electrolyte material of the first embodiment, the molar ratio (i.e., molar fraction) of the total amount of Li, Ca, Y, Sm, X and O relative to the total amount of all elements constituting the solid electrolyte material is 90% or more. As an example, the molar ratio may also be 95% or more. The solid electrolyte material of the first embodiment may also be composed only of Li, Ca, Y, Sm, X and O.

[0026] In order to improve the ionic conductivity of the solid electrolyte material, X may also be Cl or Br.

[0027] In order to improve the ion conductivity of the solid electrolyte material, the solid electrolyte material of the first embodiment may further contain at least one selected from Gd, Sr, Ba, Al, Sc, Ga, Bi, La, Zr, Hf, Ta and Nb.

[0028] The transition metal contained in the solid electrolyte material of the present embodiment may be only Y and Sm, in addition to the elements contained as inevitable impurities.

[0029] The molar ratio A of O to the total of Y and Sm in the surface region of the solid electrolyte material of the first embodiment may also be greater than the molar ratio B of O to the total of Y and Sm in the entire solid electrolyte material. Such a solid electrolyte material has high ion conductivity. As an example, the value of the molar ratio A may also be 5 times or more of the value of the molar ratio B.

[0030] Since the solid electrolyte material has high ion conductivity, the molar ratio A of the solid electrolyte material in the first embodiment may be 0.5 or more and less than 4.0.

[0031] Since the solid electrolyte material has high ion conductivity, the upper limit and lower limit of the range of the molar ratio A of the solid electrolyte material in the first embodiment may be defined by any combination of values ​​selected from 1.95, 2.44, 2.55, and 3.13.

[0032] The X-ray diffraction pattern of the first solid electrolyte material can be obtained using Cu-Kα rays. In the obtained X-ray diffraction pattern, peaks may also exist in the range of diffraction angles 2θ of 14.8° to 16.0°, 16.2° to 17.4°, 28.8° to 29.9°, 30.0° to 31.1°, 32.1° to 33.3°, 39.0° to 40.3°, and 46.9° to 48.1°. This solid electrolyte material has high ion conductivity.

[0033] In order to improve the ion conductivity of the solid electrolyte material, the following four mathematical formulas may also be satisfied.

[0034] 2.7≤x≤3.5,

[0035] 0.09≤y≤0.12,

[0036] 1.2≤z≤2.1, and

[0037] 2.8≤w≤4.4,

[0038] here,

[0039] x represents the molar ratio of Li to the total of Y and Sm,

[0040] y represents the molar ratio of Ca to the total of Y and Sm,

[0041] z represents the molar ratio of Br to the total of Y and Sm,

[0042] w represents the molar ratio of Cl to the total of Y and Sm.

[0043] In order to further improve the ion conductivity of the solid electrolyte material, the following four mathematical formulas may also be satisfied.

[0044] 3.0≤x≤3.2,

[0045] 0.09≤y≤0.12,

[0046] 1.4≤z≤1.9, and

[0047] 3.1≤w≤4.0.

[0048] The molar ratio of O to the total of Y and Sm in the entire solid electrolyte material of the first embodiment may be greater than 0 and 0.37 or less.

[0049] In order to improve the ion conductivity of the solid electrolyte material, the molar ratio of O to the total of Y and Sm may be greater than 0 and less than 0.24. The molar ratio of O to the total of Y and Sm may be greater than 0 and less than 0.05. The molar ratio of O to the total of Y and Sm may be greater than 0 and less than 0.01.

[0050] The shape of the solid electrolyte material of the first embodiment is not limited. Examples of the shape are needle-shaped, spherical, or ellipsoidal. The solid electrolyte material of the first embodiment may also be particles. The solid electrolyte material of the first embodiment may also be formed in a pellet or plate shape.

[0051] When the shape of the solid electrolyte material of the first embodiment is a particle shape (for example, a spherical shape), the solid electrolyte material of the first embodiment may have a median particle size of 0.1 μm to 100 μm.

[0052] In order to improve the ion conductivity of the solid electrolyte material of the first embodiment and to disperse the solid electrolyte material and active material of the first embodiment well, the median particle size may be 0.5 μm to 10 μm. The median particle size refers to the particle size at which the cumulative volume reaches 50% in the volume-based particle size distribution. The volume-based particle size distribution is measured, for example, using a laser diffraction measuring device or an image analysis device.

[0053] <Method for producing solid electrolyte material>

[0054] The solid electrolyte material of the first embodiment can be produced by the following method.

[0055] First, raw material powders are prepared and mixed so as to obtain a target composition.

[0056] When making a solid electrolyte material composed of Li, Ca, Y, Sm, Br, Cl and O, LiCl raw material powder, LiBr raw material powder, YCl3 raw material powder, SmCl3 raw material powder and CaBr2 are mixed. The obtained mixed powder is fired in an inert gas atmosphere (for example, an argon atmosphere with a dew point of less than -60°C) with adjusted oxygen concentration and water concentration. The firing temperature can also be, for example, 200°C to 650°C. The obtained fired product is allowed to stand in an atmosphere with a higher dew point (for example, a dry atmosphere with a dew point of -30°C).

[0057] Next, it is fired at a temperature below the melting point (e.g., 400°C), for example, in an inert gas atmosphere (e.g., an argon atmosphere with a dew point below -60°C) in which the oxygen concentration and the water concentration are adjusted. By firing at a temperature below the melting point, the proportion of O in the surface area of ​​the solid electrolyte material increases. The raw material powders can also be mixed at a pre-adjusted molar ratio in a manner that offsets composition changes that may occur during the synthesis process. The amount of oxygen in the solid electrolyte material is determined by the selection of the raw material powder, the oxygen concentration in the atmosphere, the water concentration in the atmosphere, and the reaction time. In this way, the solid electrolyte material of the first embodiment is obtained.

[0058] The raw material powder to be mixed may also be oxides and halides. For example, Y2O3, Sm2O3, NH4Cl, NH4Br, LiCl, LiBr, CaCl2 and CaBr2 may also be used as raw material powder.

[0059] It is considered that the oxygen constituting the solid electrolyte material of the first embodiment enters from the atmosphere having a relatively high dew point.

[0060] (Second embodiment)

[0061] The second embodiment will be described below. Matters described in the first embodiment may be omitted as appropriate.

[0062] The battery of the second embodiment includes a positive electrode, a negative electrode, and an electrolyte layer. The electrolyte layer is disposed between the positive electrode and the negative electrode. At least one selected from the positive electrode, the electrolyte layer, and the negative electrode contains the solid electrolyte material of the first embodiment.

[0063] Since the battery of the second embodiment contains the solid electrolyte material of the first embodiment, it has excellent charge and discharge characteristics.

[0064] Figure 1 A cross-sectional view showing a battery 1000 according to a second embodiment.

[0065] The battery 1000 includes a positive electrode 201 , an electrolyte layer 202 , and a negative electrode 203 . The electrolyte layer 202 is disposed between the positive electrode 201 and the negative electrode 203 .

[0066] The positive electrode 201 includes positive electrode active material particles 204 and solid electrolyte particles 100 .

[0067] The electrolyte layer 202 contains an electrolyte material (eg, a solid electrolyte material).

[0068] The negative electrode 203 includes negative electrode active material particles 205 and solid electrolyte particles 100 .

[0069] The solid electrolyte particle 100 is a particle containing the solid electrolyte material of the first embodiment as a main component. The solid electrolyte particle 100 may also be a particle formed of the solid electrolyte material of the first embodiment. Here, the particle containing the solid electrolyte material of the first embodiment as a main component refers to a particle containing the solid electrolyte material of the first embodiment as the largest component in terms of mass ratio.

[0070] The positive electrode 201 contains a material capable of inserting and extracting metal ions (for example, lithium ions), such as a positive electrode active material (for example, positive electrode active material particles 204 ).

[0071] Examples of positive electrode active materials are lithium-containing transition metal oxides, transition metal fluorides, polyanionic materials, fluorinated polyanionic materials, transition metal sulfides, transition metal fluorides, transition metal oxysulfides, or transition metal oxynitrides. Examples of lithium-containing transition metal oxides are LiNi 1-d-f Co d Al f O2 (here, 0<d, 0<f and 0<(d+f)<1) or LiCoO2.

[0072] In the positive electrode 201, in order to make the positive electrode active material particles 204 and the solid electrolyte particles 100 well dispersed, the positive electrode active material particles 204 may also have a median particle size of 0.1 μm or more. Through this good dispersion, the charge and discharge characteristics of the battery 1000 are improved. In order to make lithium diffuse rapidly in the positive electrode active material particles 204, the positive electrode active material particles 204 may also have a median particle size of 100 μm or less. Due to the rapid diffusion of lithium, the battery 1000 can operate at a high output power. As described above, the positive electrode active material particles 204 may also have a median particle size of 0.1 μm to 100 μm.

[0073] In the positive electrode 201 , in order to disperse the positive electrode active material particles 204 and the solid electrolyte particles 100 well, the positive electrode active material particles 204 may have a larger median diameter than the solid electrolyte particles 100 .

[0074] To increase the energy density and output of the battery 1000 , in the positive electrode 201 , the ratio of the volume of the positive electrode active material particles 204 to the total volume of the positive electrode active material particles 204 and the solid electrolyte particles 100 may be 0.30 to 0.95.

[0075] In order to improve the energy density and output power of the battery 1000 , the positive electrode 201 may also have a thickness of 10 μm to 500 μm.

[0076] The electrolyte layer 202 contains an electrolyte material. The electrolyte material may be the solid electrolyte material of the first embodiment. The electrolyte layer 202 may be a solid electrolyte layer.

[0077] The electrolyte layer 202 may be composed only of the solid electrolyte material of the first embodiment. Alternatively, the electrolyte layer 202 may be composed only of a solid electrolyte material different from the solid electrolyte material of the first embodiment.

[0078] Examples of solid electrolyte materials different from the solid electrolyte material of the first embodiment include Li2MgX'4, Li2FeX'4, Li(Al, Ga, In)X'4, Li3(Al, Ga, In)X'6, or LiI. Here, X' is at least one selected from F, Cl, Br and I.

[0079] In the present disclosure, “(A, B, C)” means “at least one selected from A, B, and C”.

[0080] Hereinafter, the solid electrolyte material of the first embodiment is referred to as a first solid electrolyte material. A solid electrolyte material different from the solid electrolyte material of the first embodiment is referred to as a second solid electrolyte material.

[0081] The electrolyte layer 202 may contain not only the first solid electrolyte material but also the second solid electrolyte material. The first solid electrolyte material and the second solid electrolyte material may be uniformly dispersed. The layer formed by the first solid electrolyte material and the layer formed by the second solid electrolyte material may also be stacked along the stacking direction of the battery 1000.

[0082] In order to suppress short circuit between the positive electrode 201 and the negative electrode 203 and to improve the output of the battery, the electrolyte layer 202 may have a thickness of 1 μm to 1000 μm.

[0083] The negative electrode 203 contains a material capable of inserting and removing metal ions (for example, lithium ions), such as a negative electrode active material (for example, negative electrode active material particles 205 ).

[0084] Examples of negative electrode active materials are metal materials, carbon materials, oxides, nitrides, tin compounds, or silicon compounds. The metal material may be a single metal or an alloy. Examples of metal materials are lithium metal or lithium alloys. Examples of carbon materials are natural graphite, coke, graphitizable carbon, carbon fiber, spherical carbon, artificial graphite, or amorphous carbon. From the viewpoint of capacity density, preferred examples of negative electrode active materials are silicon (i.e., Si), tin (i.e., Sn), silicon compounds, or tin compounds.

[0085] In the negative electrode 203, in order to make the negative electrode active material particles 205 and the solid electrolyte particles 100 well dispersed, the negative electrode active material particles 205 may also have a median particle size of 0.1 μm or more. Through this good dispersion, the charge and discharge characteristics of the battery are improved. In order to make lithium diffuse rapidly in the negative electrode active material particles 205, the negative electrode active material particles 205 may also have a median particle size of 100 μm or less. Due to the rapid diffusion of lithium, the battery can operate at a high output power. As described above, the negative electrode active material particles 205 may also have a median particle size of 0.1 μm to 100 μm.

[0086] In the negative electrode 203 , in order to disperse the negative electrode active material particles 205 and the solid electrolyte particles 100 well, the negative electrode active material particles 205 may have a larger median diameter than the solid electrolyte particles 100 .

[0087] To increase the energy density and output of the battery 1000 , in the negative electrode 203 , the ratio of the volume of the negative electrode active material particles 205 to the total volume of the negative electrode active material particles 205 and the solid electrolyte particles 100 may be 0.30 to 0.95.

[0088] In order to improve the energy density and output power of the battery 1000 , the negative electrode 203 may also have a thickness of 10 μm to 500 μm.

[0089] In order to improve ion conductivity, chemical stability, and electrochemical stability, at least one selected from the positive electrode 201 , the electrolyte layer 202 , and the negative electrode 203 may contain a second solid electrolyte material.

[0090] As described above, the second solid electrolyte material may also be a halide solid electrolyte. Examples of halide solid electrolytes are Li2MgX'4, Li2FeX'4, Li(Al, Ga, In)X'4, Li3(Al, Ga, In)X'6, or LiI. Here, X' is at least one selected from F, Cl, Br and I.

[0091] The second solid electrolyte material may be a sulfide solid electrolyte.

[0092] Examples of sulfide solid electrolytes are Li2S-P2S5, Li2S-SiS2, Li2S-B2S3, Li2S-GeS2, Li 3.25 Ge 0.25 P 0.75 S4, or Li 10 GeP2S 12 .

[0093] The second solid electrolyte material may be an oxide solid electrolyte.

[0094] Examples of oxide solid electrolytes are:

[0095] (i) NASICON-type solid electrolytes such as LiTi2(PO4)3 or its element substitution products;

[0096] (ii) Perovskite-type solid electrolytes such as (LaLi)TiO3;

[0097] (iii)Li 14 ZnGe4O 16 , Li4SiO4, LiGeO4 or their element substitution bodies, etc. LISICON type solid electrolytes;

[0098] (iv)Li7La3Zr2O 12 or a garnet-type solid electrolyte such as an element substitution product thereof; or (v) Li3PO4 or a N substitution product thereof.

[0099] The second solid electrolyte material may also be an organic polymer solid electrolyte.

[0100] Examples of organic polymer solid electrolytes are compounds of polymer compounds and lithium salts. The polymer compounds may also have an ethylene oxide structure. The polymer compounds having an ethylene oxide structure may contain more lithium salts, thereby further improving ion conductivity.

[0101] Examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), or LiC(SO2CF3)3. One lithium salt selected from these may be used alone. Alternatively, a mixture of two or more lithium salts selected from these may be used.

[0102] At least one selected from the positive electrode 201 , the electrolyte layer 202 , and the negative electrode 203 may contain a non-aqueous electrolyte solution, a gel electrolyte, or an ionic liquid in order to facilitate the transfer of lithium ions and improve the output characteristics of the battery 1000 .

[0103] The non-aqueous electrolyte includes a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent.

[0104] Examples of non-aqueous solvents are cyclic carbonate solvents, chain carbonate solvents, cyclic ether solvents, chain ether solvents, cyclic ester solvents, chain ester solvents, or fluorine solvents. Examples of cyclic carbonate solvents are ethylene carbonate, propylene carbonate, or butylene carbonate. Examples of chain carbonate solvents are dimethyl carbonate, ethyl methyl carbonate, or diethyl carbonate. Examples of cyclic ether solvents are tetrahydrofuran, 1,4-dioxane, or 1,3-dioxolane. Examples of chain ether solvents are 1,2-dimethoxyethane or 1,2-diethoxyethane. Examples of cyclic ester solvents are γ-butyrolactone. Examples of chain ester solvents are methyl acetate. Examples of fluorine solvents are fluoroethylene carbonate, methyl fluoropropionate, fluorobenzene, ethyl fluoromethyl carbonate, or dimethylene fluorocarbonate. One non-aqueous solvent selected from them can be used alone. Alternatively, a mixture of two or more non-aqueous solvents selected from them can be used.

[0105] Examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), or LiC(SO2CF3)3. One lithium salt selected from these may be used alone. Alternatively, a mixture of two or more lithium salts selected from these may be used.

[0106] The concentration of the lithium salt is, for example, in the range of 0.5 mol / L to 2 mol / L.

[0107] As the gel electrolyte, a polymer material impregnated with a non-aqueous electrolyte solution can be used. Examples of the polymer material are polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride, polymethyl methacrylate, or a polymer having an ethylene oxide bond.

[0108] Examples of cations contained in ionic liquids are:

[0109] (i) Aliphatic chain quaternary salts such as tetraalkylammonium or tetraalkylphosphonium;

[0110] (ii) an aliphatic cyclic ammonium such as pyrrolidinium, morpholinium, imidazolinium, tetrahydropyrimidinium, piperazinium or piperidinium; or

[0111] (iii) Nitrogen-containing heterocyclic aromatic cations such as pyridinium and imidazolium cations.

[0112] An example of an anion contained in an ionic liquid is PF6 - 、BF4 - 、SbF6 - 、AsF6 - 、SO3CF3 - 、N(SO2CF3)2 - 、N(SO2C2F5)2 - 、N(SO2CF3)(SO2C4F9) - , or C(SO2CF3)3 - .

[0113] The ionic liquid may also contain a lithium salt.

[0114] At least one selected from the positive electrode 201 , the electrolyte layer 202 , and the negative electrode 203 may contain a binder for the purpose of improving the adhesion between particles.

[0115] The example of binder is polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, aramid resin, polyamide, polyimide, polyamide-imide, polyacrylonitrile, polyacrylic acid, polymethyl acrylate, polyethyl acrylate, polyhexyl acrylate, polymethacrylic acid, polymethyl methacrylate, polyethyl methacrylate, polyhexyl methacrylate, polyvinyl acetate, polyvinyl pyrrolidone, polyether, polyether sulfone, hexafluoropolypropylene, styrene-butadiene rubber, or carboxymethyl cellulose. Copolymer can also be used as binder. The example of this binder is a copolymer of two or more materials selected from tetrafluoroethylene, hexafluoroethylene, hexafluoropropylene, perfluoroalkyl vinyl ether, vinylidene fluoride, chlorotrifluoroethylene, ethylene, propylene, pentafluoropropylene, fluoromethyl vinyl ether, acrylic acid and hexadiene. Mixture selected from two or more thereof can also be used as binder.

[0116] At least one selected from the positive electrode 201 and the negative electrode 203 may contain a conductive auxiliary agent in order to improve electronic conductivity.

[0117] Examples of conductive additives are:

[0118] (i) Graphites such as natural graphite or artificial graphite;

[0119] (ii) Carbon blacks such as acetylene black or Ketjen black;

[0120] (iii) conductive fibers such as carbon fibers or metal fibers;

[0121] (iv) fluorinated carbons;

[0122] (v) Metal powders such as aluminum;

[0123] (vi) Conductive whiskers such as zinc oxide or potassium titanate;

[0124] (vii) conductive metal oxides such as titanium oxide; or

[0125] (viii) Conductive polymer compounds such as polyaniline, polypyrrole or polythiophene. For cost reduction, the conductive auxiliary agent described in (i) or (ii) above may be used.

[0126] Examples of the shape of the battery of the second embodiment include a coin shape, a cylindrical shape, a square shape, a sheet shape, a button shape, a flat shape, or a laminated shape.

[0127] The battery of the second embodiment can also be manufactured, for example, by preparing a positive electrode forming material, an electrolyte layer forming material, and a negative electrode forming material, and producing a stacked body in which a positive electrode, an electrolyte layer, and a negative electrode are arranged in this order by a known method.

[0128] Example

[0129] Hereinafter, the present disclosure will be described in more detail with reference to Examples.

[0130] (Example 1)

[0131] [Production of solid electrolyte materials]

[0132] In an argon atmosphere having a dew point below -60°C and an oxygen concentration below 0.0001% by volume (hereinafter referred to as a "dry argon atmosphere"), LiCl, LiBr, YCl3, SmCl3 and CaBr2 are prepared as raw material powders in a molar ratio of LiCl:LiBr:YCl3:SmCl3:CaBr2=1:1.8:0.8:0.2:0.1. These materials are crushed and mixed in a mortar. The resulting mixture is calcined in an alumina crucible at 500°C for 1 hour and then crushed in a mortar. The resulting calcined product is allowed to stand for about 10 minutes in a dry atmosphere having a dew point of -30°C and an oxygen concentration below 20.9% by volume. Next, it is calcined in a dry argon atmosphere at 400°C for 1 hour and then crushed in a mortar. In this way, the solid electrolyte material of Example 1 is obtained.

[0133] [Composition analysis of solid electrolyte materials]

[0134] The contents of Li, Ca, Sm and Y per unit weight of the solid electrolyte material of Example 1 were measured using a high-frequency inductively coupled plasma emission spectrometry analyzer (manufactured by Thermo Fisher Scientific, iCAP7400) by high-frequency inductively coupled plasma emission spectrometry. The contents of Br and Cl in the solid electrolyte material of Example 1 were measured using an ion chromatograph (manufactured by Dionex, ICS-2000) by ion chromatography. Based on the contents of Li, Ca, Y, Sm, Br and Cl obtained from these measurement results, the molar ratio of Li:Ca:Y:Sm:Br:Cl was calculated. As a result, the solid electrolyte material of Example 1 had a molar ratio of Li:Ca:Y:Sm:Br:Cl of 3.06:0.10:0.80:0.20:1.90:4.00.

[0135] The mass of O relative to the mass of the solid electrolyte material of Example 1 was measured by non-dispersive infrared absorption method using an oxygen-nitrogen-hydrogen analyzer (manufactured by Horiba, Ltd., EMGA-930). As a result, the mass ratio of O was 0.05%. Based on this, the molar ratio of (Y+Sm):O was calculated. As a result, the solid electrolyte material of Example 1 had a molar ratio of (Y+Sm):O of 1.00:0.01.

[0136] The molar ratio of O to the total of Y and Sm in the surface region of the solid electrolyte material of Example 1 was measured using a scanning X-ray photoelectron spectrometer (manufactured by Ulvac-phi, PHI Quantera SXM) using X-ray photoelectron spectroscopy. Al rays were used as the X-ray source. As a result, the solid electrolyte material of Example 1 had a molar ratio of (Y+Sm):O of 1.00:1.95 in the surface region. The surface region of the present disclosure refers to the region measured in this way. The thickness of the surface region of the solid electrolyte material of the first embodiment is about 5 nm from the surface of the solid electrolyte material to the inside.

[0137] In the composition analysis, an element having a molar fraction of less than 0.01% with respect to the total of Y and Sm is regarded as an impurity.

[0138] [X-ray diffraction]

[0139] The X-ray diffraction pattern of the solid electrolyte material of Example 1 was measured using an X-ray diffractometer (Rigaku MiniFlex600) in a dry environment with a dew point of -45°C or less. Cu-Kα rays (wavelength and ).

[0140] As a result of X-ray diffraction measurement, peaks were found at 15.36°, 16.72°, 22.82°, 28.59°, 29.31°, 30.48°, 32.64°, 39.62°, 47.43°, and 51.90°. Figure 2 Graph showing the X-ray diffraction pattern of the solid electrolyte material of Example 1.

[0141] [Evaluation of ion conductivity]

[0142] Figure 3 A schematic diagram of a press mold 300 used to evaluate the ion conductivity of a solid electrolyte material is shown. The press mold 300 includes a punch upper portion 301, a frame mold 302, and a punch lower portion 303. The frame mold 302 is formed of insulating polycarbonate. The punch upper portion 301 and the punch lower portion 303 are both formed of electronically conductive stainless steel.

[0143] use Figure 3 The press molding die 300 shown was used to measure the ion conductivity of the solid electrolyte material of Example 1 by the following method.

[0144] In a dry argon atmosphere, the powder of the solid electrolyte material of Example 1 is filled in the interior of the press mold 300. In the interior of the press mold 300, the solid electrolyte material of Example 1 (i.e. Figure 3 A pressure of 400 MPa is applied on the powder 101 of the solid electrolyte material using the punch upper part 301 and the punch lower part 303.

[0145] The punch upper part 301 and the punch lower part 303 are connected to a potentiostat (VersaSTAT4 manufactured by Princeton Applied Research) while maintaining the pressure. The punch upper part 301 is connected to the working electrode and the potential measurement terminal. The punch lower part 303 is connected to the counter electrode and the reference electrode. The impedance of the solid electrolyte material of Example 1 is measured at room temperature using electrochemical impedance spectroscopy.

[0146] Figure 4 Graph showing a Cole-Cole plot of the solid electrolyte material of Example 1 obtained by impedance measurement.

[0147] Figure 4 In the example, the real value of the impedance at the measurement point where the absolute value of the phase of the complex impedance is the smallest is regarded as the resistance value of the solid electrolyte material of Example 1 with respect to ion conduction. For this real value, please refer to Figure 4 The arrow R SE Using this resistance value, the ion conductivity was calculated based on the following mathematical formula (1).

[0148] σ=(R SE ×S / t) -1 (1)

[0149] Here, σ is the ion conductivity. S is the contact area between the solid electrolyte material and the upper portion 301 of the punch ( Figure 3 , which is equivalent to the cross-sectional area of ​​the hollow portion of the frame mold 302). SE is the resistance value of the solid electrolyte material in the impedance measurement. t is the thickness of the solid electrolyte material after the pressure is applied ( Figure 3 , which is equal to the thickness of the layer formed by the powder 101 of the solid electrolyte material).

[0150] The ionic conductivity of the solid electrolyte material of Example 1 measured at 25°C was 1.6×10 -3 S / cm.

[0151] [Battery production]

[0152] In a dry argon atmosphere, the solid electrolyte material of Example 1 and LiCoO2 as an active material were prepared so as to have a volume ratio of 70:30. These materials were mixed in an agate mortar to obtain a mixture.

[0153] In an insulating cylinder having an inner diameter of 9.5 mm, the solid electrolyte material of Example 1 (100 mg), the above mixture (12.0 mg) and aluminum powder (14.7 mg) were stacked in order. A pressure of 300 MPa was applied to the stack to form the first electrode and the solid electrolyte layer. The solid electrolyte layer had a thickness of about 500 μm.

[0154] Next, a metal In foil was stacked on the solid electrolyte layer. The solid electrolyte layer was sandwiched between the metal In foil and the first electrode. The metal In foil had a thickness of 200 μm. Next, a pressure of 80 MPa was applied to the metal In foil to form the second electrode.

[0155] A current collector made of stainless steel was mounted on the first electrode and the second electrode, and then a current collecting lead was mounted on the current collector. Finally, an insulating metal hoop (ferrule) was used to block the inside of the insulating tube from the outside air atmosphere, thereby sealing the inside of the tube. In this way, the battery of Example 1 was obtained.

[0156] [Charge and discharge test]

[0157] Figure 5 : is a graph showing the initial discharge characteristics of the battery of Example 1. The charge and discharge test was performed as follows.

[0158] The battery of Example 1 was placed in a constant temperature chamber at 25°C.

[0159] At 91μA / cm 2 The battery of Example 1 was charged at a current density of 200 % to a voltage of 3.7 V. This current density is equivalent to a 0.05C rate.

[0160] Next, at 91 μA / cm 2 The battery of Example 1 was discharged at a current density of until a voltage of 1.9V was reached.

[0161] As a result of the charge and discharge test, the battery of Example 1 had an initial discharge capacity of 759 μAh.

[0162] (Examples 2 to 4)

[0163] In Example 2, the solid electrolyte material of Example 2 was obtained in the same manner as in Example 1 except that the time for leaving the reactants in a dry atmosphere having a dew point of -30°C and an oxygen concentration of 20.9 vol % or less was set to 2 hours instead of about 10 minutes.

[0164] In Example 3, the time for standing the reactants in a dry atmosphere having a dew point of -30°C and an oxygen concentration of 20.9 vol % or less was set to 36 hours instead of about 10 minutes. A solid electrolyte material of Example 3 was obtained in the same manner as in Example 1 except for this.

[0165] In Example 4, the reaction product was allowed to stand in a dry atmosphere having a dew point of -30°C and an oxygen concentration of 20.9 vol % or less for 100 hours instead of about 10 minutes. The solid electrolyte material of Example 4 was obtained in the same manner as in Example 1 except for this.

[0166] The element ratio (molar ratio), X-ray diffraction, and ion conductivity of the solid electrolyte materials of Examples 2 to 4 were measured in the same manner as in Example 1. Tables 1 and 2 show the measurement results. Figure 2 It is a graph showing the X-ray diffraction patterns of the solid electrolyte materials of Examples 2 to 4.

[0167] The mass ratios of O in Examples 2 to 4 relative to the entire solid electrolyte material were 0.17%, 1.02% and 1.55%, respectively.

[0168] Batteries of Examples 2 to 4 were obtained in the same manner as in Example 1 using the solid electrolyte materials of Examples 2 to 4.

[0169] Using the batteries of Examples 2 to 4, charge and discharge tests were carried out in the same manner as in Example 1. Like the battery of Example 1, the batteries of Examples 2 to 4 were able to be charged and discharged satisfactorily.

[0170] (Comparative Example 1)

[0171] In a dry argon atmosphere, LiCl and FeCl2 were prepared as raw material powders in a molar ratio of LiCl:FeCl2=2:1. These materials were ground using a planetary ball mill in a mechanochemical reaction for 25 hours at 600 rpm. In this way, the solid electrolyte material of Comparative Example 1 was obtained. The solid electrolyte material of Comparative Example 1 is a known halide solid electrolyte material having a composition represented by Li2FeCl4.

[0172] The ion conductivity of the solid electrolyte material of Comparative Example 1 was measured in the same manner as in Example 1. As a result, the ion conductivity measured at 22° C. was 9×10 -6 S / cm.

[0173] A battery of Comparative Example 1 was obtained in the same manner as in Example 1 using the solid electrolyte material of Comparative Example 1.

[0174] Using the battery of Comparative Example 1, a charge and discharge test was carried out in the same manner as in Example 1. The battery of Comparative Example 1 had an initial discharge capacity of only 1 μAh or less. In other words, the battery of Comparative Example 1 could neither be charged nor discharged. Figure 5 It is a graph showing the initial discharge characteristics of the battery of Comparative Example 1.

[0175] Table 1

[0176]

[0177] Table 2

[0178]

[0179] <Investigation>

[0180] Table 1 shows that the solid electrolyte materials of Examples 1 to 4 have a 1×10 -5 High ion conductivity of more than S / cm.

[0181] Examples 1 to 4 show that if the molar ratio of O to Y and Sm in the solid electrolyte material as a whole is greater than 0 and less than 0.37, the solid electrolyte material has a 1×10 -5 S / cm or more. Comparing Examples 1 and 2 with Examples 3 and 4, it is shown that if the molar ratio is greater than 0 and less than 0.05, the solid electrolyte material has a 1×10 -3 S / cm or higher ion conductivity.

[0182] Examples 1 to 4 show that the molar ratio of O to the total of Y and Sm in the surface region of the solid electrolyte material is 6 times greater than the molar ratio of O to the total of Y and Sm in the entire solid electrolyte material.

[0183] Depend on Figure 2 The X-ray diffraction patterns shown and Table 2 show that the crystal structure of the solid electrolyte material changes due to the different contents of O. In addition, Table 1 shows that as the content of O increases, the contents of Br and Cl decrease. Therefore, it can be considered that O replaces Br and Cl and enters the crystal structure.

[0184] The batteries of Examples 1 to 4 can be charged and discharged at 25°C.

[0185] Since the solid electrolyte materials of Examples 1 to 4 do not contain sulfur, hydrogen sulfide is not generated.

[0186] As described above, the solid electrolyte material of the present disclosure is suitable for providing a battery having high lithium ion conductivity and capable of good charge and discharge.

[0187] Industrial Applicability

[0188] The solid electrolyte material disclosed in the present invention can be used in, for example, an all-solid lithium ion secondary battery.

[0189] Explanation of symbols:

[0190] 100 Solid electrolyte particles 101 Powder of solid electrolyte material

[0191] 201 positive electrode 202 electrolyte layer

[0192] 203 Negative electrode 204 Positive electrode active material particles

[0193] 205 Negative electrode active material particles 300 Pressurized molding die

[0194] 301 Punch upper part 302 Frame mold

[0195] 303 punch lower part 1000 battery

Claims

1. A solid electrolyte material comprising Li, Ca, Y, Sm, X and O, Here, X is at least one selected from F, Cl, Br and I, The molar ratio of O to the total of Y and Sm in the surface region of the solid electrolyte material is greater than the molar ratio of O to the total of Y and Sm in the entire solid electrolyte material. In the X-ray diffraction pattern obtained by X-ray diffraction measurement using Cu-Kα rays, peaks exist in the ranges of diffraction angle 2θ of 14.8° to 16.0°, 16.2° to 17.4°, 28.8° to 29.9°, 30.0° to 31.1°, 32.1° to 33.3°, 39.0° to 40.3°, and 46.9° to 48.1°.

2. The solid electrolyte material according to claim 1, wherein X is Cl and Br.

3. The solid electrolyte material according to claim 1 or 2, further comprising at least one selected from the group consisting of Gd, Sr, Ba, Al, Sc, Ga, Bi, La, Zr, Hf, Ta and Nb.

4. The solid electrolyte material according to claim 1 or 2, which satisfies the following four mathematical formulas: 2.7≤x≤3.5、 0.09≤y≤0.12、 1.2≤z≤2.1, and 2.8≤w≤4.4, here, x represents the molar ratio of Li to the total of Y and Sm, y represents the molar ratio of Ca to the total of Y and Sm, z represents the molar ratio of Br to the total of Y and Sm, w represents the molar ratio of Cl to the total of Y and Sm.

5. The solid electrolyte material according to claim 1 or 2, wherein The molar ratio of O to the total of Y and Sm in the entire solid electrolyte material is greater than 0 and is equal to or less than 0.

37.

6. A battery comprising: positive electrode, Negative electrode, and an electrolyte layer disposed between the positive electrode and the negative electrode, in, At least one selected from the positive electrode, the negative electrode, and the electrolyte layer contains the solid electrolyte material according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Method of manufacturing sulfide solid electrolyte material, sulfide solid electrolyte material, and lithium battery

    JP2011129312A

  • Solid electrolyte material, and cell

    WO2018025582A1

  • Solid electrolyte material, and battery

    WO2019135343A1

  • Sulfide-based solid electrolyte particles

    WO2019176895A1